Effect of natural safe rock minerals on growth, yield and quality of rice (Oryza sativa) in rice-wheat cropping system - RANVA, SANTOSH; SINGH, Y V; JAIN, NEELAM; BANA, RAMESH C; BANA, R S; BAJYA, DEWA RAM (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted during two Kharif seasons of 2016 and 2017 at the research farm of ICARIndian Agricultural Research Institute, New Delhi to study the effect of Safe Rock Mineral (SRM) on productivity and quality of rice in rice-wheat cropping system. The experiment was carried out in randomized block design with three replications involving two rice (Oryza sativa) establishment methods (aerobic rice and transplanted rice) and six crop nutrition levels on rice-wheat sequence. The results indicate that, in general transplanted rice performed comparatively better in terms of growth, yield and quality parameters compared to aerobic rice. Different nutritional level improved the productivity of rice and succeeding wheat crop in both the years significantly. Among nutrient management practices, highest plant growth, yield attributes and yield of rice were obtained with the application of SRM application @ 250 kg/ha + 100% RDF and it was followed by No SRM application + 100% RDF, SRM application @ 250 kg/ha + 50% RDF (Chemical) + 25% RDF (Organic-FYM) and SRM application @ 250 kg/ha + 50% RDF (Organic-FYM). Integrated nutrient management with SRM application @ 250 kg/ha + 100% RDF increased grain protein content significantly over only SRM application @ 250 kg/ha. An increase of 16.42% and 18.07% in grain protein was recorded under aerobic and transplanted method of rice, respectively. It was concluded that integrated application of SRM @ 250 kg/ha + 100% RDF gave the highest growth and productivity of rice and with this treatment grain yield was 32.2% and 32.9% higher than only SRM application at @ 250 kg/ha under aerobic and transplanted conditions respectively.